Perspective on High‐Concentration Electrolytes for Lithium Metal Batteries. Issue 5 (7th February 2021) - Jiang, Gaoxue; Li, Fang; Wang, Huaping; Wu, Mingguang; Qi, Shihan; Liu, Xinhua; Yang, Shichun; Ma, Jianmin
Abstract : Nonaqueous electrolytes play important roles in determining the performance of lithium‐ion batteries. However, the high flammability, poor thermal stability, narrow electrochemical window, and slow electrode reaction kinetics seriously hinder the application of batteries. Compared with traditional electrolytes, high‐concentration electrolytes (HCEs) have a higher ion transfer number, wider electrochemical window, higher thermal stability, low volatility, good flame resistance, and passivation of Al current collector at high potential. The HCEs can effectively overcome the shortcomings of traditional electrolytes, and provide a new direction for the development of next‐generation batteries. Therefore, it is very timely to write a perspective on HCEs for directing future research. Herein, the recent development of HCEs is described. Abstract : Herein, the recent development of high‐concentration electrolytes for lithium metal batteries is described, and the future research directions are discussed.